Licencing and training reform in the Australian aircraft maintenance industry. (2nd July 2016) - Hampson, Ian; Fraser, Doug
Abstract: The training and licencing of aircraft maintenance engineers fulfils a crucial protective function since it is they who perform and supervise aircraft maintenance and certify that planes are safe afterwards. In Australia, prior to training reform, a trades-based system of aircraft maintenance engineer training existed in an orderly relation with the system of licencing, regulated by the Civil Aviation Safety Authority (CASA). Training reform through the 1990s gave rise to concerns that the training system could not be relied upon to deliver adequate numbers of trainees with valid qualifications. From 2007, CASA introduced new regulations, designed to align Australia's qualifications and licencing with the European Aviation Safety Agency (EASA). This process saw the aviation regulator effectively cede much quality control of training to an increasingly dysfunctional training system, giving rise to doubts about whether Australia's international obligations for quality aircraft maintenance training can be fulfilled.